ALTERNATIF TATA LETAK FASILITAS (MESIN) MENGGUNAKAN CELLULAR MANUFACTURING SYSTEM DI UD. TRI REJEKI, MADIUN - Anisa, Nurfa (JURNAL AGRI-TEK, 2014)
Facility layout (machine) is industry engineering and basic main in industry, as procedure arrangement of physical facilities plant to support fluency production.Based on condition faced by UD. Tri Rejeki, Madiun, then to get facility layout with a pattern efficient flow used approach Cellular Manufacturing System (CMS), as basic facility layout. The purpose of this research to give alternative facility layout from grouping machine-part of CMS with Algorithm Heuristic method, so it can cut the gap material handling, and known efficiency reduction distances and reduction costs material handling. The results show that method of Algorithm Heurictic Complete Linkage Clustering (CLC) elected the best method, occur reduction distances being 552,92 m/day and reduction costs being Rp 76.817,16/day. Where the value of efficiency distances and efficiency costs are 17,30%.Keywords : Facility Layout, Cellular Manufacturing System, Material Handling